Pembaharuan Nahwu menurut Shauqi Dhaif dan Ibrahim Musthafa - Fatkhur Roji (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2020)
Nahwu is the basis of Arabic science that emerged in the first century hijrah. then nahwu widespread evidenced by the many books the study of nahwu that discuss the methods in it, coupled with the emergence of groups that perform particular approach since the second century hijrah, trigger group basroh, Kufa, Baghdad, andalus and groups of Egyptians until adab to five hijrah. The efforts made by them have made nahwu increasingly broad and deep so difficult for students in modern times. In this modern century has seemed the efforts of Arabic linguists to reconstruct the Arabic language to be easily understood by modern scholars in both the Arab and non Arab. On this occasion, the researchers chose the famous reformer and has been the concern of many scholars of Arabic and also as a member of the Al-Arabiyah Majmaul lughah namely Ibrahim Musthofa and Syauqi dhoif. Researchers presented two problems, first what is the basic foundation of Ibrahim Musthofa and Syauqi dhoif in doing an update nahwu. Both what similarities and differences both in the renewal of the thoughts nahwu. The purpose of this study was to determine two issues that have been asked by the researcher.This research includes research literature that uses character study approach. As for who becomes the primary source in this study was the Book of Ibraham Musthofaالنحو‌ إحياء  bouquet and النحو‌ جديد Syauqi dhoif bouquet. The data obtained were analyzed in two stages, the first stage using taxonomic analysis and the second using comparative analysis.The results of this study indicate underlying Ibrahim Musthofa nahwu reform efforts with this approach is similar to the meaning and thought JR Firth, Syauqi dhoif underlying reform efforts nahwunya with phonological approach shows the influence of the thought of Bloomfield. As for the aspect of equality in the concept of renewal is refused their term far'iyah address in i'rob, they also negate chapter وأخواهتا ‌كان ,وأخواتها ‌كان in chapter al-marfu 'at, they also agreed that isim that occur afterوأخواتها ظن not اإلسنادي ‌تركيب ,Aspects of the differences between them can be summarized from the foundation of the reform and in preparing several chapters nahwu.